The Educational Inspectorate in Spain and the initial training of the headmasters: a revision from the model of Aragon - Barrio Bastida, Eloy; Lorente Lorente, Ángel (Avances en Supervisión Educativa, 2018)
From the analysis of the initial training model that has been offered to the newer headmasters in the Aragonese Autonomous Region (Spain) in the last 7 years. A contrast to its conclusions is being considered from the contributions that have been made by the educational research, the international reports and the Spanish framework for the good management, with the purpose of considering new initial training models where the pedagogical leadership of the headmasters will be more important than now. Moreover, the importance of the educational inspectorate in the design, development and assessment of an initial training of the school headmasters that strengthen such leadership is being assessed.